Paclitaxel-based regimens as first-line treatment in advanced gastric cancer. (April 2015) - Guo, Zengqing; Wang, Xiaojie; Lin, Rongbo; Chen, Ling; Fan, Nanfeng; Chen, Yu; Lin, Jinyuan; Yu, Jiami
Abstract : The aim of this study was to evaluate the efficacy and safety of paclitaxel-based regimens as first-line treatments in advanced gastric cancer. We reviewed 397 previously untreated patients with advanced gastric cancer, who non-randomly received one of three paclitaxel-based regimens: paclitaxel plus fluorouracil/leucovorin (PF), paclitaxel plus oxaliplatin (PO), and paclitaxel plus oxaliplatin plus fluorouracil/leucovorin (POF) between January 2003 and December 2010. The PF, PO, and POF response rates were 47·13, 52·08, and 63·78%, respectively. Overall survivals (OS) were 11·2, 11·7, and 11·7 months, respectively. Progression-free survivals (PFS) were 6·6, 7·2, and 7·1 months, respectively. Leucopenia was higher on the triplet regimen than the doublet regimens. The paclitaxel-based regimens appeared to be effective in patients with advanced gastric cancer. The triplet regimen produced a higher response rate than either doublet regimen with more side effects, while survivals were similar among all three treatments.